Deep Brain Stimulator Device Infection: The Mayo Clinic Rochester Experience. (26th December 2022) - Tabaja, Hussam; Yuen, Jason; Tai, Don Bambino Geno; Campioli, Cristina Corsini; Chesdachai, Supavit; DeSimone, Daniel C; Hassan, Anhar; Klassen, Bryan T; Miller, Kai J; Lee, Kendall H; Mahmood, Maryam
Abstract: Background: Deep brain stimulator (DBS)–related infection is a recognized complication that may significantly alter the course of DBS therapy. We describe the Mayo Clinic Rochester experience with DBS-related infections. Methods: This was a retrospective study of all adults (≥18 years old) who underwent DBS-related procedures between 2000 and 2020 at the Mayo Clinic Rochester. Results: There were 1087 patients who underwent 1896 procedures. Infection occurred in 57/1112 (5%) primary DBS implantations and 16/784 (2%) revision surgeries. The median time to infection (interquartile range) was 2.1 (0.9–6.9) months. The odds of infection were higher with longer operative length ( P = .002), higher body mass index (BMI; P = .006), male sex ( P = .041), and diabetes mellitus ( P = .002). The association between infection and higher BMI ( P = .002), male sex ( P = .016), and diabetes mellitus ( P = .003) remained significant in a subgroup analysis of primary implantations but not revision surgeries. Infection was superficial in 17 (23%) and deep in 56 (77%) cases. Commonly identified pathogens were Staphylococcus aureus (65%), coagulase-negative staphylococci (43%), and Cutibacterium acnes (45%). Three device management approaches were identified: 39 (53%) had complete device explantation, 20 (27%) had surgical intervention with device retention, and 14 (19%) had medical management alone. Treatment failure occurred in 16 (23%) patients. Time-to-event analysis showed fewer treatment failures with complete device explantation ( P = .015). Only 1 individual had complications with brain abscess at failure. Conclusions: Primary DBS implantations had higher rates of infection compared with revision surgeries. Complete device explantation was favored for deep infections. However, device salvage was commonly attempted and is a reasonable approach in select cases given the low rate of complications. Abstract : Deep brain stimulator infections typically occur within a few months of device placement or revision, with the majority caused by Staphylococcal species or Cutibacterium acnes. Early, complete device removal was associated with better outcomes than device retention.